Peran Tokoh Agama dalam Pencegahan Penyalahgunaan Narkoba di Nagari Ujung Gading Kecamatan Lembah Melintang Kabupaten Pasaman Barat - Rini Febriani; Noor Fadlli Marh (ALSYS, 2026)
Although the role of religious leaders in preventing drug abuse has been examined in various studies, research specifically addressing their synergy with the police, the village government, Kerapatan Adat Nagari (KAN), and youth organizations at the village level remains limited. This study aimed to describe the role of religious leaders in preventing drug abuse in Ujung Gading Village, Lembah Melintang Subdistrict, West Pasaman Regency. This study employed a qualitative approach with a descriptive design. The research informants consisted of religious leaders, police officers, village government officials, traditional leaders, and youth organization administrators selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which comprises data reduction, data display, and conclusion drawing. The results showed that religious leaders played an important role in preventing drug abuse through Islamic preaching, religious lectures, religious study sessions, moral development, and coordination with various stakeholders. Cross-sector synergy was manifested through educational activities, public awareness campaigns, deliberations, and community development initiatives that strengthened social control based on religious and customary values. However, the effectiveness of prevention efforts continued to face constraints in the form of low participation among some community members, the influence of peer environments, and limited family involvement. These findings reinforce the relevance of Erving Goffman’s Dramaturgical Theory in explaining the role of religious leaders as social actors who build legitimacy, convey moral messages, and develop cross-sector collaboration. This study contributes to the development of the sociology of religion and provides practical implications for local governments, religious institutions, customary institutions, and communities in strengthening community-based drug abuse prevention strategies.